Neurofibromatosis‐associated malignant peripheral nerve sheath tumors in children have a worse prognosis: A nationwide cohort study. Issue 4 (30th December 2019) - Martin, Enrico; Coert, J. Henk; Flucke, Uta E.; Slooff, Willem‐Bart M.; van de Sande, Michiel A.J.; van Noesel, Max M.; Grünhagen, Dirk J.; Wijnen, Marc H.W.A.; Verhoef, Cornelis
Abstract: Background: Malignant peripheral nerve sheath tumors (MPNST) are rare and aggressive non‐rhabdomyoblastic soft‐tissue sarcomas (NRSTS) in children. This study set out to investigate clinical presentation, treatment modalities, and factors associated with survival in pediatric MPNST using Dutch nationwide databases. Methods: Data were obtained from the Netherlands Cancer Registry (NCR) and the Dutch Pathology Database (PALGA) from 1989 to 2017. All primary MPNSTs were collected. Demographic differences were analyzed between adult and pediatric (age ≤18 years) MPNST. In children, demographic and treatment differences between neurofibromatosis type 1 (NF1) and non‐NF1 were analyzed. A Cox proportional hazard model was constructed for localized pediatric MPNSTs. Results: A total of 70/784 MPNST patients were children (37.1% NF1). Children did not present differently from adults. In NF1 children, tumor size was more commonly large (> 5 cm, 92.3% vs 59.1%). Localized disease was primarily resected in 90.6%, and radiotherapy was administered in 37.5%. Non‐NF1 children tended to receive chemotherapy more commonly (39.5% vs 26.9%). Overall, estimated five‐year survival rates of localized NF1‐MPNST was 52.4% (SE: 10.1%) compared with 75.8% (SE: 7.1%) in non‐NF1 patients. The multivariate model showed worse survival in NF1 patients (HR: 2.98; 95% CI, 1.17‐7.60, P  = 0.02) and increased survival in patients diagnosed after 2005 (HR: 0.20; 95% CI, 0.06‐0.69, P  = 0.01). No treatment factors were independently associated with survival. Conclusion: Pediatric MPNSTs have presentations similar to adult MPNSTs. In children, NF1 patients present with larger tumors, but are treated similarly to non‐NF1 MPNSTs. In localized pediatric MPNST, NF1 is associated with worse survival. Promisingly, survival has increased for pediatric MPNSTs after 2005.